ANALISIS STRATEGI PEMBELAJARAN, PENDEKATAN PEMBELAJARAN, MOTODE PEMBELAJARAN, DAN MODEL PEMBELAJARAN DI UPTD SD GMIT 27 MEBUNG - Yuliyanti Etde; Yessy Mata (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study aims to analyze the learning strategies, learning approaches, learning methods, and learning models implemented at UPTD SD GMIT 27 Mebung. This research employed a qualitative approach with a descriptive research design. Data were collected through observations, interviews, and documentation involving teachers and classroom learning activities. The results indicate that teachers at UPTD SD GMIT 27 Mebung have implemented various learning strategies tailored to the characteristics of the students. The learning approach applied is student-centered learning, while the dominant learning methods include lecturing, question and answer, discussion, and assignments. The learning models used include cooperative learning and contextual learning. The implementation of these strategies, approaches, methods, and learning models is considered sufficiently effective in increasing students’ activeness and understanding in the learning process.